Subsurface water retention membrane (SWRM)/ Soil Water Retention Technology (SWRT) to restore and use sustainably, lands with sandy soils - CGIAR Research Program on Water, Land and Ecosystems (2020)
Michigan State University (MSU) designed SWRT/SWRM to retain water and nutrients in the root zone. It had not been tested in Africa. WLE/Alliance and partners are testing and piloting SWRT/SWRM in Kenya and Zimbabwe; results will be used to explore how to scale it sustainably in the countries and beyond.